THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND DEATH ANXIETY IN THE ELDERLY UNDERGOING HEMODIALYSIS - Erti I Dewi; Benaya Sriharja; Fitrio Deviantony; Enggal Hadi Kurniyawan; Yeni Fitria (UNEJ e-Proceeding, 2023)
Background. Hemodialysis therapy can raise stressors which are able to cause death anxiety due to the occurrence of comorbidities after renal failure which are unavoidable even though undergoing hemodialysis. The purpose of this study was to investigate the relationship between family support and death anxiety in the elderly who were undergoing hemodialysis. Method. This study used a quantitative research technique with a cross-sectional approach. To determine the sample, a total sampling technique was adopted with the sample size of 43 people. Results. The measurement instruments used in this study were the family support questionnaire to measure family support with the (r) value of 0.97 and reliability value of 0.85, and the death anxiety questionnaire to measure death anxiety with the validity value of 0.367-0.724 and reliability value of 0.806. The respondents consisted of 32 elderly men and 11 elderly women. Hypothesis testing using Chi Square with the analysis between family support and death anxiety revealed the p value = 0.000, which means that there was a relationship between family support and anxiety level in the elderly who were undergoing hemodialysis. Conclusion. Family support has an important role in reducing the level of pressure in dealing with problems. Optimal family support can reduce death anxietyin the elderly who are undergoing hemodialysis.